2005
DOI: 10.1094/pd-89-1048
|View full text |Cite
|
Sign up to set email alerts
|

Seed Transmission of Wheat streak mosaic virus Shown Unequivocally in Wheat

Abstract: Under conditions that excluded any possibility of eriophyid mite vector activity, seed transmission of Wheat streak mosaic virus (WSMV) was shown in eight different wheat genotypes at rates of 0.5 to 1.5%. Virus identification in seedlings came from characteristic symptoms in wheat, enzyme-linked immunosorbent assay with WSMV-specific antibodies, reverse-transcription polymerase chain reaction tests with WSMV-specific primers, and cDNA sequence comparisons with published sequences. Sequence comparisons of four… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
37
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(41 citation statements)
references
References 12 publications
0
37
1
3
Order By: Relevance
“…Furthermore, absence of data does not demonstrate that this lineage was not present in other locations that could have served as a source. With respect to the second explanation, WSMV isolates from Australia are seed borne at 0.5-2% [2,11], a rate several log units greater than that previously reported for WSMV in maize [9]. However, as other Presented is a neighbor-joining tree based on 1,000 bootstrap iterations and rooted with the complete sequence of oat necrotic mottle virus (ONMV) designated as the outgroup.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, absence of data does not demonstrate that this lineage was not present in other locations that could have served as a source. With respect to the second explanation, WSMV isolates from Australia are seed borne at 0.5-2% [2,11], a rate several log units greater than that previously reported for WSMV in maize [9]. However, as other Presented is a neighbor-joining tree based on 1,000 bootstrap iterations and rooted with the complete sequence of oat necrotic mottle virus (ONMV) designated as the outgroup.…”
mentioning
confidence: 86%
“…Analysis of 3 0 -proximal partial nucleotide sequences [2] indicated that Australian isolates of WSMV were closely related to each other, and also to certain Clade D isolates from the American Pacific Northwest (APNW). As several of the Australian isolates are seed borne in wheat at low frequency [2,11], infected seed has been implicated as the means of initial introduction. Subsequent spread of WSMV within Australia was likely due to both seed transmission and vector transmission by the wheat curl mite [8].…”
mentioning
confidence: 99%
“…Around 50% of viruses affecting leguminous crops are seed-borne , whereas in small-grain cereals, only two are recorded so far (Diekmann & Putter, 1995;Jones, Coutts, Mackie, & Dwyer, 2005). Where seed transmission rates are high, as with PSbMV in pea, use of healthy seed is an effective control measure (Hampton, 1984).…”
Section: Healthy Seedsmentioning
confidence: 99%
“…Yes, Razvyazkina (1975) [16], Oleinik (1968) [17] argued that WSMV is not transmitted by seeds. Later in the scientific literature, there were reports of WSMV extending from the seed that caused the epidemic prevalence of the disease [18,19,20]. These data, as some scientists need to view the issue of Epidemiology streak mosaic virus and its spread wheat with sowing material and material genetics bank [21].…”
Section: Fig 3 Electron Virions Wsmv Found In Leaves Of Winter Wheamentioning
confidence: 99%